2010
DOI: 10.4161/chan.4.1.10562
|View full text |Cite
|
Sign up to set email alerts
|

Swapping the I-II intracellular linker between L-type CaV1.2 and R-type CaV2.3 high-voltage gated calcium channels exchanges activation attributes

Abstract: (2010) Swapping the I-II intracellular linker between L-type Ca V 1.2 and Rtype Ca V 2.3 high-voltage gated calcium channels exchanges activation attributes, Channels, 4:1, 42-50,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…As observed in the GV relations of our channel chimeras, our data exhibits similar trends with mutations that increase the PL helical propensity or the effect of Ca V ␤ binding, i.e., a leftward shift. Similar trends were observed in a recent report where the first 70 I-II linker residues were interchanged between Ca V 1.2 and Ca V 2.3 (Gonzalez-Gutierrez et al, 2010). Nonetheless, the persistent effects of the PL mutations in the absence of Ca V ␤ indicate that this region, independent of the binding of Ca V ␤, has helical secondary structure rather than random coil.…”
Section: Discussionsupporting
confidence: 87%
“…As observed in the GV relations of our channel chimeras, our data exhibits similar trends with mutations that increase the PL helical propensity or the effect of Ca V ␤ binding, i.e., a leftward shift. Similar trends were observed in a recent report where the first 70 I-II linker residues were interchanged between Ca V 1.2 and Ca V 2.3 (Gonzalez-Gutierrez et al, 2010). Nonetheless, the persistent effects of the PL mutations in the absence of Ca V ␤ indicate that this region, independent of the binding of Ca V ␤, has helical secondary structure rather than random coil.…”
Section: Discussionsupporting
confidence: 87%
“…Structure-function studies have shown that β binding at the alpha interaction domain (AID) of I-II loop induces a coil-to-helix conformation of the proximal linker, strengthening the connection between the pore and the β subunit/I-II loop complex (Opatowsky et al, 2004;Van Petegem et al, 2004;Arias et al, 2005;Findeisen and Minor, 2009;Almagor et al, 2012). Proximal linker structure integrity is thought to be essential for β-dependent modulation of α 1 gating but its role in the localization of the channel has been less investigated (Findeisen and Minor, 2009;Gonzalez-Gutierrez et al, 2010;Almagor et al, 2012). So according to these data, the n2368 mutation in IS6 could possibly disrupt the proximal linker integrity, decreasing β modulation of channel inactivation and α 1 trafficking.…”
Section: Research Articlementioning
confidence: 99%
“…All β-subunit variants, except for the short splice forms β 4c (Hibino et al, 2003) and β 1d , (Cohen et al, 2005) and a few others found in the heart (Foell et al, 2004), share this architecture (Figure 3). Association of the β-subunit with the AID site induces a coil-to-helix transition in the AID region that likely extends to the S6 segment of the first repeat (Findeisen and Minor, 2009; Gonzalez-Gutierrez et al, 2010). Although a clear mechanism of how the β-subunit facilitates pore opening or forward trafficking of the channel was not readily deducible from the three-dimensional structures, these studies opened up new scenarios to explain β-modulation.…”
Section: Beta Subunitmentioning
confidence: 99%
“…Since cytoplasmic loops start as an extension of the sixth segment of each repeat, they are likely to influence channel gating. We swapped the I–II loop of the poorly coupled Ca V 1.2 channel with the efficiently coupled Ca V 2.3 and found that these phenotypes were transferred independently of β-subunit interaction (Gonzalez-Gutierrez et al, 2010). When the β-subunit is present, the coupling efficiency is sensitive to the residues within the AID domain that are exposed to the milieu (Gonzalez-Gutierrez et al, 2008a).…”
Section: Beta Subunitmentioning
confidence: 99%